Investigation of medical intervention with fatal outcome: the impact of post-mortem CT and CT angiography - Heinemann, Axel (Radiol Med, 2015)
Post-mortem computed tomography (PMCT) has been proven for its appropriateness to become an integral part of routine pre-autoptic forensic investigations either in the field of forensic investigation of fatal medical error or in hospital quality management. The autoptic investigation of unexpected and peri-interventional deaths can be usefully guided by post-mortem imaging which offers significant added value in the documentation of misplacement of medical devices before dissection with the risk of artificial relocation and the detection of iatrogenic air embolism. Post-mortem CT angiography (PMCTA) augments PMCT in the search for sources of hemorrhages and for the documentation of vascular patency and unimpaired perfusion after general and cardiovascular surgery or transvascular catheter-assisted interventions. Limitations of PMCT and PMCTA in medical error cases are method-related or time-dependent including artifacts by early post-mortem tissue change. Thromboembolic complications including pulmonary embolism, the differentiation of ante- and post-mortem coagulation and the detection of myocardial infarction remain areas with compromised diagnostic efficiency as compared to autopsy. Furthermore, extended survival periods after a complication in question impedes visualization of contrast agent extravasation at vascular leakage sites. PMCT and PMCTA contribute substantially for proving a correct interventional approach and guide forensic or clinical autopsy in the reconstruction of adverse medical events with fatal outcome. Post-mortem imaging could also assume a new role as an alternative in a clinicopathological setting if autopsy is not achievable when the probability in the individual case is acceptable to answer specific questions.